PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Rahayu, Krisnawati Wiji (EKONOMIA, 2017)
Influence Motivation Work To Performance Officer at the Secretariat of the East Kutai Regency is the extent to which the work motivation affects employee performance and employee willingness to devote the skills, knowledge, skills, energy and time in which the work motivation expect compensation from the company that can satisfy their needs.The formulation of the problem in this research is